Implementation of culturally responsive teaching based digital media to enhance reading skills of elementary school students - Ivanka, Afrilia Bayu; Pratiwi, Cerianing Putri; Listiani, Ivayuni (Universitas Ahmad Dahlan, 2025)
This research aims to (1) Describe the implementation of digital media with culturally responsive perceptions to improve the reading skills of fourth-grade elementary school students and (2) describe the supporting and inhibiting factors in the application of digital media with culturally responsive perceptions in reading instruction in fourth-grade elementary school. This research uses a classroom action research design conducted in two cycles. The subjects of the study are 15 fourth-grade elementary school students. The research procedures include planning, action implementation, observation, and reflection stages. Data collection techniques are observation, interviews, tests, and documentation. Data is analyzed descriptively quantitatively and qualitatively based on the improvement of scores and student engagement. The research results show that the application of digital media based on Culturally Responsive Teaching improves students' reading skills from the pre-cycle to cycle I and cycle II. The improvement is evident in students' literal, interpretive, and evaluative understanding aspects. Media that connects the reading content with the students' culture has been shown to enhance interest and active participation in the learning process. The conclusion of this study states that the Culturally Responsive Teaching-based learning approach supported by digital media can create a more meaningful, contextual, and inclusive learning experience. This research contributes to the development of pedagogical practices in elementary schools by integrating digital technology and culturally responsive learning approaches. These results can serve as a reference for teachers, media developers, and education policy makers in designing literacy strategies that are relevant to the social and cultural contexts of students.